Clinical Comparative Study for Some Biochemical Changes in Sera of Pregnant with Iron Deficiency Anemia (Medico Legal Update, 2020)
The aim of this study was to study the evaluation of serum oxidation in pregnant women with iron deficiencyanemia by measuring lipid oxidation (MDA), and antioxidant status by analogy (Ferritin).Also, Examinationof erythropoietin (EPO) levels in pregnancy with iron deficiency anemia. Blood samples were obtainedfrom (80) pregnant women with anemia divided according to the stage of pregnancy and iron deficiency asfollows: 20 patients in the second third with anemia without iron deficiency, 20 patients in the second thirdwith anemia with iron deficiency, 20 patients In the third trimester with anemia without iron deficiency, 20patients in the third trimester have anemia with iron deficiency. In addition to (40) healthy pregnant womenas a control group. Divided into two groups, 20 patients in the second trimester and 20 patients in the thirdtrimester.Results: The results show a presence of a significant increase in MDA and EPO in all groups of patients inIron deficiency in comparison with control group. But, Ferritin levels showed a significant decrease in allgroups of patients in Iron deficiency and Iron normal comparison with control group.